N400 Effects Reflect Activation Spread during Retrieval of Arithmetic Facts - Niedeggen, Michael; Rösler, Frank (Psychological science, 1999)
Arithmetic facts are stored in densely interconnected memory networks, and retrieval errors may occur because activation spreads to associated results. We studied the extension of activation spread by means of the so-called N400 effect of the event-related brain potential (ERP). With semantic stimuli, N400 amplitude has proved to be inversely proportional to the amount of activation that originates from a priming context. ERPs were recorded from 61 scalp positions while 16 subjects verified 600 multiplication problems (a × b = c). The solution to each problem could be correct or incorrect. Incorrect solutions were either table related to one of the operands (e.g., 5 × 8 = 32, 24, or 16) or unrelated (e.g., 5 × 8 = 34, 26, or 18), and were either a small, medium, or large numerical distance from the correct product. Our findings suggest that activation spread in an arithmetic memory network is restricted to numbers that are table related to one of the operands and that are numerically plausible.